Does environmental regulation promote urban economic resilience? A case of China's Yangtze River Economic Belt - Jie Zhou; Haipeng Chen; Jiewei Liu; Qianling Shen; Dungang Zang (Sustainable Futures)
Environmental regulation is an essential issue affecting urban economic resilience(UER) as it balances sustainable development and environmental protection. This paper uses a fixed effects model to analyze the impact of environmental regulation on UER in the Yangtze River Economic Belt. The results show that the strengthening of environmental regulation can positively enhance UER, and this positive effect is attributable to a boost in industrial structure optimization. Regional heterogeneity is manifested by the most significant effect in the midstream region. The findings contribute to enhancing the UER in developing countries to provide theoretical support and policy implications for future economic sustainable development.